Comparison of Eutectic Mixture of Local Anesthesia Cream and Subcutaneous Lidocaine to Reduce Chest Tube Removal Pain and Willingness to Repeat Procedure - Roman Diaz; Yusup Subagio Sutanto; Ahmad Farih Raharjo (Jurnal Respirologi Indonesia, 2022)
Background:. Patients with chest tube have allodynia (pain from stimuli that is normally painless) and hyperalgesia (increased sensitivity to pain). Anesthetics has not been used routinely when removing chest tubes assuming that the procedure is brief and that the pain is short-lived, even though it could be the most painful part of chest tube procedures.Objective: This study compared the effectiveness of local anesthetic EMLA cream and subcutaneous infiltration of lidocaine to reduce pain of chest tube removal, 10 minutes after, and it’s effect on the patient's willingness to repeat the procedure.Method: A quasi-experimental clinical trial conducted on 28 patients undergoing chest tube removal at dr. Moewardi from September 2020. The EMLA group (n = 14) received 2 grams of topical EMLA cream applied 2 hours before chest tube removal. The lidocaine group (n = 14) received subcutaneous infiltration of 2% lidocaine 5 minutes before chest tube removal. Pain was measured by VAS pain before, during, and 10 minutes after the chest tube was removed, followed by filling out a willingness to repeat procedure questionnaire.Results: Topical EMLA cream was comparable to 2% lidocaine infiltration for reducing pain during chest tube removal (p = 0.679) and 10 minutes thereafter (p = 0.833). EMLA cream did not increase the patient's willingness to repeat the procedure (p = 0.815)Conclusion: Topical EMLA cream able to replace the subcutaneous infiltration of 2% lidocaine as a local anesthetic for chest tube removal but does not increase the patient's willingness to repeat the procedure.